Tax Law Enforcement In Strengthening Tax Compliance Behavior Of Individual Taxpayers - Edrick. P. Putra; Heru Tjaraka (Jurnal Akuntansi, 2020)
The main problem of taxation in Indonesia still revolves around the tax compliance level, which is low, the problem of tax compliance is a classic problem faced by almost all countries. Departing from the general taxation problem, this study specifically examines taxpayers in Central Kalimantan, specifically in Palangkaraya. The research questions raised are whether the interaction between tax awareness and tax law enforcement impact on strengthening taxpayer compliance behavior. Second, whether the interaction between trust in tax authority and tax law enforcement has an impact on strengthening taxpayer compliance behavior. The test results show that both tax awareness and trust in tax authority have a positive influence on the taxpayer obedient behavior. The tax law enforcement moderation variable is tested to be a moderation variable that reinforces the taxpayer's compliance behavior. In the final section we offer conclusions, contributions, and implications, including suggestions for further research.